Antibiotics self-medication practices among students in Universitas Prima Indonesia - Novriani, Erida; Neswita, Elfia; Razoki, Razoki (Jurnal Prima Medika Sains, 2023)
The irrational use of antibiotics can endanger health by causing unwanted drug reactions, side effects, and drug resistance. This study aimed to analyze the patterns of antibiotic self-medication among university students. This descriptive cross-sectional study was conducted at Prima Indonesia University in October 2023. A total of 307 randomly selected students from various faculties (health science clumps and non-health science clumps) filled out questionnaires distributed via Google Forms. The collected data are then analyzed descriptively to obtain frequency and percentage data, which are then presented in the form of tables and narratives. The results showed that about 83.39% of respondents had used antibiotics before. Most respondents used antibiotics because they were easily available (43.36%) or because of their previous experience (36.72%). The most common conditions for antibiotic use were cough and cold (47.66%), and infections (23.05%). Most respondents used antibiotics based on doctor ’sor pharmacist’s recommendations (45.31%). The duration of antibiotic use was 1-3 days (61.72%), followed by 4-7 days (31.64%) and more than 7 days (6.64%). Antibiotics were purchased from pharmacies (83.20%). The most common reactions to the overuse of antibiotics were nausea and vomiting (40.23%) and headache (32.81%). Most respondents (53.13%) consulted a doctor or pharmacist if they experienced reactions to antibiotic overuse.